(untitled) (TAJ: Journal of Teachers Association, 2011)
Teaching is a highly complex process. The medical teaching is more complex and difficult. There are certain basic skills of teaching e.g. the way the teacher presents lecture, use various teaching media, use of basic questionnaire and motivation etc. Besides these basic skills there are certain microskills of teaching. These are explaining, introductory procedure, closures and advanced questioning. Out of these microskills, explaining is the most important and powerful skill. Explaining has some components; e.g. clarity, fluency of language, use of illustration, variation of voice manners, structuring statements and finally obtaining feedback. Every medical teacher should use these microskills in the lecture room for effective teaching. DOI: http://dx.doi.org/10.3329/taj.v14i2.8397 TAJ 2001; 14(2): 96-98